PENGARUH KECERDASAN EMOSIONAL, EFIKASI DIRI DAN KREATIVITAS GUNA MENINGKATKAN KINERJA KARYAWAN PT. REX DENPASAR - Ida Ayu Putu Dian Harta Mahita; Made Ika Prastyadewi; I Nyoman Resa Adhika (VALUES, 2023)
Employee performance is the most important thing in human resource management because it is one of the factors that determine the success of the company. Employee performance is a work result that is given by an individual to the company or organization where they work by providing maximum work results to the company and a result of work or work performance carried out by a person or group of people in carrying out their functions in accordance with the responsibilities given to them. The purpose of this research is to analyze the influence of emotional intelligence, self-efficacy and creativity to improve employee performance. This research was conducted at PT. REX Denpasar. The number of samples is 42 employees, with saturated sampling method. Data was collected through observation, interviews and questionnaires. The data analysis technique used is multiple linear regression. Based on the results of the analysis that has been processed, it is found that all the hypotheses proposed are accepted. Emotional intelligence has a positive and significant effect on employee performance at PT. REX Denpasar, self-efficacy has a positive and significant effect on employee performance at PT. REX Denpasar and creativity have a positive and significant effect on employee performance at PT. REX Denpasar. Suggestions for further research can develop this research by adding other variables to this study.